Exploring the Cultural DaÔÇÖwah Strategy of Hadrah Al-Jiduri Art: A Phenomenological Study on Character Building - Afandi, Ahmad Muzakki; Arifin, Zainul (Journal of Islamic Education Students (JIES), 2025)
The Hadrah Al-Jiduri art, rooted in the local Islamic tradition of ahlussunnah wal jamaÔÇÖah, serves as a cultural daÔÇÖwah strategy that not only preserves religious values but also fosters character building. This study aims to explore how the Hadrah Al-Jiduri community applies collective leadership, regional coordination, youth involvement, routine gatherings, and major religious events to shape moral traits such as humility (tawadhuÔÇÖ), consistency (istiqomah), love for the Prophet Muhammad SAW, tolerance, discipline, and spiritual awareness. Using a qualitative descriptive method with a phenomenological approach, data were collected through interviews, observations, and document analysis, then analyzed using Miles and HubermanÔÇÖs interactive model with triangulation for validity. The findings show that the structured and participatory practices of Hadrah Al-Jiduri effectively integrate local cultural wisdom into daÔÇÖwah activities, providing a replicable model for strengthening religious character and communal harmony.┬á┬á